ANALISIS PENGARUH IMPLEMENTASI QRIS TERHADAP PENINGKATAN VOLUME TRANSAKSI UMKM DI INDONESIA TAHUN 2020–2025” - Awang, Risqi; Walidain, M. Sulton Rosyid Birrul; Mubarok, Rizky; Hidayat, Mohammad Wahyu Dwi; Wahjono, Sentot Imam (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The rapid development of digital payment technology in Indonesia has significantly transformed the financial transaction ecosystem, particularly for Micro, Small, and Medium Enterprises (MSMEs). The Quick Response Code Indonesian Standard (QRIS), launched by Bank Indonesia in 2019 and widely implemented from 2020 onwards, represents a strategic government initiative to accelerate financial inclusion and modernize payment systems. This study aims to analyze the influence of QRIS implementation on the increase in MSME transaction volume in Indonesia during the period 2020–2025. Using a quantitative approach with secondary data drawn from Bank Indonesia reports, the Financial Services Authority (OJK), the Ministry of Cooperatives and SMEs, and relevant academic literature, the study employs descriptive statistical analysis and trend analysis to examine growth patterns. The findings indicate a significant positive correlation between expanding QRIS adoption and rising MSME transaction volume, with registered QRIS merchants growing from approximately 6 million in 2020 to over 50 million by 2024. Key enabling factors include ease of use, low implementation cost, government digital literacy programs, and the acceleration caused by the COVID-19 pandemic which pushed consumer behavior toward contactless payments. Challenges remain, including uneven digital infrastructure in rural areas and low financial literacy among certain MSME segments. The study concludes that QRIS has been a transformative instrument for MSME financial inclusion and recommends continued policy support, infrastructural investment, and tailored financial literacy programs to sustain and expand its positive impact.